Actively Open-Minded Thinking About Evidence (AOT-E) Scale: Adaptation and Evidence of Validity in a Brazilian Sample - Andressa Bonafé-Pontes; Rafael Costa Bastos; Ronaldo Pilati (Judgment and Decision Making)
The present study aimed to adapt the actively open-minded thinking about evidence (AOT-E) scale to Brazilian Portuguese and assess its psychometric properties and nomological network in a Brazilian sample. It begins by investigating the underlying content structure of the AOT-E in its original form. Results from an exploratory factor analysis (EFA) of secondary data serve as the basis for the proposed adaptation, which is subjected to both EFA and confirmatory factor analysis (CFA). A total of 718 participants from various regions of Brazil completed an online survey that included the AOT-E, along with other instruments that allowed for an assessment of the scale’s nomological network, including measures of science literacy, attitude toward science, conspiracy beliefs, and religiosity. The EFA and CFA of both the original and Brazilian samples suggested a unidimensional solution. Despite the differences found in a multigroup CFA, polychoric correlations provided evidence of expected nomological relationships that replicate international findings. Overall, this study contributes to expanding the availability of adapted and validated research instruments in non-WEIRD samples.